Peningkatan Hasil Belajar Matematika melalui Penerapan Model Pembelajaran Accelerated Learning Tipe Message (Mindset, Entrance, Switch-Ownership, Store, Act, Go-again, Engage) pada Peserta Didik Kelas 5 SDN Dukuh Kupang V Surabaya - Mohamad Reza Muji Ashari; Jarmani Jarmani; Endang Supriyatin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to improve mathematics learning outcomes in flat volume material through the application of the MESSAGE Type Accelerated Learning learning model (Mindset, Entrance, Switch-Ownership, Store, Act, Go-again, Engage) in grade 5 students at SDN Dukuh Kupang V Surabaya . The method used in this research is Classroom Action Research (PTK) which is carried out in two cycles, each consisting of planning, implementation, observation and reflection. The research results showed a significant increase in students' mathematics learning outcomes. In the pre-cycle, the percentage of student learning completion only reached 55%. After implementing the MESSAGE learning model in cycle I, the percentage of student learning completion increased to 70%. In cycle II, the percentage of student learning completeness further increased to 85%. This increase shows that the application of the MESSAGE Type Accelerated Learning learning model is effective in improving mathematics learning outcomes regarding volume of plane shapes in class 5 students. Based on the results of this research, it is concluded that the use of the MESSAGE learning model can increase student involvement and facilitate better understanding of concepts, thus having a positive impact on their mathematics learning outcomes. It is recommended for educators to consider using this model as an alternative in teaching mathematics.